Does denosumab exert a protective effect against COVID-19? Results of a large cohort study - Cassibba, Sara; Ippolito, Silvia; Pellegrini, Silvia; Trevisan, Roberto; Rossini, Alessandro (Frontiers in Endocrinology, 2023)
Denosumab is a monoclonal antibody blocking the Receptor Activator of Nuclear Factor Kappa-Β/Receptor Activator of Nuclear factor Kappa-Β Ligand (RANK/RANKL) pathway, thus inhibiting osteoclastogenesis. Since RANK and RANKL are also involved in the immune system activation, denosumab might interfere with the response against infections. Our study aimed to explore the relationship between denosumab treatment and coronavirus disease 2019 .Occurrence and severity of COVID-19 were recorded in consecutive patients referring to the Endocrinology Department of Papa Giovanni XXIII Hospital, Bergamo, from 1 st January 2020 to 1 st January 2021. Patients treated with denosumab were compared to outpatient controls. Patients' features were summarized by descriptive statistics. Multivariate logistic regression assessed the relationship between denosumab and COVID-19 adjusting for potential confounders. Subgroups analyses according to age, sex, body mass index (BMI), smoking status, and vitamin D levels were performed.The final population included 331 patients treated with denosumab and 357 controls. COVID-19 incidence was lower in denosumab group (7.6% vs. 14.6%, p=0.004). COVID-19 severity was similar in both groups. Multiple logistic regression confirmed an association between denosumab and a reduced occurrence of symptomatic COVID-19 (OR 0.46, 95% CI 0.21-0.98, p-value 0.049).Subgroup analyses suggested a potential protective effect of denosumab in patients over 75 years (OR 0.12, 95% CI 0.02 -0.6, p=0.011), with a significant interaction between denosumab and age categories (p=0.047).Our study confirms that denosumab may be safely continued in COVID-19 patients. RANK/RANKL inhibition seems associated to a reduced incidence of symptomatic COVID-19, particularly among the elderly.